Exploring Motives and Strategies in the Production of Knowledge in the University Context by the Example of Academic Career Trajectories (Global Journal of Human-Social Science, 2023)
Current research has shown that the combination of implicit and explicit knowledge among various actors is particularly crucial to the production of knowledge and that the characteristics of social relationships and resulting networks impact on how proficienty is acquired, transferred, absorbed, and applied. Although investigations have suggested that the actors involved in knowledge production are active and strategic agents, who differ considerably in their abilities to incorporate and generate knowledge, they are mostly referred to in terms as nodes or black boxes. In this regard, relationship research has demonstrated that actors differ in terms of motivations and abilities to share information and knowledge. Such motives are often strategic.
Keywords: knowledge production; tacit knowledge; university research; social relationships; qualitative research; knowledge transfer; knowledge acquisition